Analisis Pengembangan Lokasi Apartemen Menggunakan Analytic Hierarchy Process berbasis Sistem Informasi Geografis - Dedy Kurnia Sunaryo; Endro Yuwono; Sentot Achmadi; Tiara DE; Geoghalvin Almeriq Audolfy Caecarma (E-Jurnal Universitas Samudra, 2025)
East Java has Malang City as the second-largest city. Common problems that occur in big cities in Indonesia are overcrowding and increasingly limited land. The solution to this problem is to develop vertical housing types such as apartments and flats. The need for new apartment development as a response to high public demand, by creating an analytical hierarchy process and a system for apartment developers, will assist apartment developers in making decisions. With AHP, you can determine the suitability of the apartment construction location with supporting parameters, namely slope maps, road network accessibility maps, existing land use maps, spatial pattern maps, distance maps to public facilities, and water availability maps. The results of the analysis of the suitability of apartment development in the city of Malang using AHP and GIS are then studied for the suitability of land use against the RTRW so that the implementation and development of apartment development in the city of Malang are according to plan. So that decision-making can be relevant and make the city of Malang an ideal city.